THE AFFORDABILITY ASSESSMENT TO IMPLEMENT LIGHT RAIL TRANSIT (LRT) FOR GREATER YOGYAKARTA - , ANJANG NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An increasing trend each year of private vehicle ownership in Greater Yogyakarta has affected the traffic condition. Trans Jogja bus as a new public transport, which was designed better than local bus, has not operated optimally. This condition has brought up a plan to introduce Light Rail Transit (LRT). As the first indication that the LRT can be built in Greater Yogyakarta, the transportation affordability index was used to understand whether the LRT tariff was affordable. The first step was calculating the affordability index of the existing modes for comparison. Then, the potential passengers were forecasted using gravity model so that the possible route was able to be proposed. Each proposed route was analysed using Multi Criteria Decision Analysis (MCDA) method to decide which route that would be built first. Using the chosen route, the tariff of LRT was calculated based on Permen no 28/2012 as government policy about determining railway tariff and was used to know the affordability index of LRT. The result showed that the Trans Jogja was affordable while the motorcycle was not affordable. There were four routes proposed to serve the 1611017 potential trips in Greater Yogyakarta forecasted in 2019. The line T1 has been chosen as the first LRT route to be built and gave the LRT tariff of IDR 2500 per trip. Therefore, the affordability index of Tram Jogja for people with average income was 10.66% while for people with bottom quartile income was 13.56%. In conclusion, the Tram Jogja was the most affordable transport mode in Greater Jogja.